Faculty Participation in Asynchronous Learning Networks: A Case Study of Motivating and Inhibiting Factors - Schifter, Catherine C. (Online Learning, 2000)
This case presents and compares the top five motivating and inhibiting factors for faculty participation in Asynchronous Learning Networks (ANL) or distance education (DE) as reported by faculty participators and non-participators, and administrators. While faculty and administrators agreed strongly on what inhibits faculty from participating in ALN/DE programs, there were significantly different perceptions on what motivates faculty to participate across the three groups. For ALN/DE programs to succeed, faculty participation is imperative; therefore, program administrators need to understand why faculty participate.